Model for responsive agriculture hub via e-commerce to sustain food security - Wan Ab. Rahman, Wan Nurhayati; Wan Zulkifli, Wan Nurfarah; Zainuri, Nur Nabilah; Anwar, Hanis Amira Khairol (Science and Information Organization, 2024)
Ensuring food security in the face of evolving environmental, economic, and societal challenges requires innovative solutions that leverage emerging technologies. This paper proposes a model for a responsive agriculture hub facilitated through e-commerce platforms to address the dynamic demands of food production, distribution, and consumption. The model integrates data-driven decision-making, supply chain optimization, and digital marketplaces to enhance the efficiency and resilience of agricultural systems. By harnessing real-time data analytics, predictive algorithms, and smart logistics, the proposed hub enables agile responses to fluctuating market conditions, climatic variability, and resource constraints. Through case studies and simulation analyses, we demonstrate the effectiveness of the model in enhancing the accessibility, affordability, and sustainability of food systems. Furthermore, we discuss the implications of this approach for stakeholders across the agricultural value chain, including farmers, distributors, retailers, and consumers. The findings underscore the potential of leveraging e-commerce platforms as catalysts for transformative change in agriculture, contributing to the overarching goal of achieving food security in an increasingly uncertain world.